High-risk twin pregnancy: case report of an adolescent patient with cystic fibrosis and systemic lupus erythematosus - Paula Baptista Sanseverino; Anneliese Hoffmann; Sandra Machado; Mariana Farias; Marcus Silva Michels; Maria Teresa Vieira Sanseverino; Paulo José Cauduro Marostica (Journal of Medical Case Reports, 2022)
Abstract Background We present the first case to our knowledge of a spontaneous twin pregnancy in a 16-year-old Caucasian patient with cystic fibrosis and systemic lupus erythematosus. Cystic fibrosis is one of the most common autosomal recessive genetic disorders and primarily affects the respiratory and digestive systems. Systemic lupus erythematosus is a chronic inflammatory disease of unknown cause that affects nearly every organ. Patients with cystic fibrosis or systemic lupus erythematosus are progressively having longer life expectancy and better quality of life, which has led a greater number of female patients reporting the desire to become mothers. Case presentation We present a case of a Caucasian 16-year-old pregnant with twins being treated for both cystic fibrosis and systemic lupus erythematosus. She has two CFTR mutations: p.F508del and 1812_1G>A. In the second trimester, she was admitted for possible preterm labor, which was successfully stopped. The patient’s nutritional status worsened, and she had a pulmonary exacerbation as well as a flare of systemic lupus erythematosus. At the 28th gestational week, she presented with a massive hemoptysis episode. The cesarean delivery had no complications, and there were no serious immediate postpartum complications. Discussion and conclusions While adolescent pregnancies in and of themselves are considered high risk for both the young mothers and their children, they are further complicated when the mother has two chronic diseases and a twin pregnancy. We achieved positive results using a multidisciplinary approach; however, the risks involved were so high that major efforts are to be taken by our medical community to prevent unplanned pregnancies in all patients with cystic fibrosis, especially when a serious comorbidity like the one in this case is present.